Biological activities and DNA interactions of aqueous extract of Phlomis linearis (Boiss. & Bal.) - Betül Aydın; Lütfiye Yasemin Gönder; Nebahat Aytuna Çerçi; Yiğit Can Ateş; İlayda Sezin Yalçınkaya; Nüveyre Canbolat; Leyla Açık; Nurcan Karacan; Emine Akyüz Turumtay; Halbay Turumtay (International Journal of Plant Based Pharmaceuticals, 2023)
Phlomis linearis Boiss. & Bal. of the Lamiaceae family is one of the endemic species in Turkey, i.e., growing in the east, central, and southeast parts of Anatolia and used for herbal tea. This study was designed to identify the biochemical and bioactivity properties of this endemic species by DPPH scavenging activity, metal chelating activity, total phenolic content, HPLC-DAD analysis, and MTT assay. Furthermore, the plant extract was evaluated for its antimicrobial activity against bacteria and fungi by using the microdilution method. The interactions between extract and plasmid DNA and their restriction endonuclease reactions were investigated by agarose gel electrophoresis. To support our hypothesis, we performed a molecular docking analysis. The DPPH scavenging activity of the plant extract was 53.86 ± 0.50 µg/ml in terms of IC50 value. The IC50 value of the plant extract was determined as 14.71 ± 4.01 mg/ml for metal chelating assay. The phenolic content of the extract was 231.55 ± 2.11 mg/g dry weight expressed as gallic acid equivalents (GAE). HPLC-DAD results revealed that the phenolic compounds were mainly derivatives of rosmarinic acid, chlorogenic acid, luteolin, luteolin-7-glycoside, luteolin derivatives, rutin derivatives, and apigenin derivatives. Besides, the cytotoxic activity of the plant extract against L929 fibroblast, H1299 non-small-cell lung carcinoma, and Caco-2 colorectal adenocarcinoma cell lines was determined by MTT assay. Phenolic content and molecular docking results correlated with each other.